The Effect of Plant Growth-Promoting Fungal Species on Tef [Eragrostis tef (Zucc.) Trotter] Growth, Yield, and Grain Nutrient Uptake - Tsegaye, Zerihun (The Indonesian Forestry Certification Cooperation, 2025)
This study investigates the impact of plant growth-promoting fungi (PGPF) on the growth, yield, and nutrient uptake of tef (Eragrostis tef). We evaluated the effects of three fungal species—Trichoderma harzianum Rifai BGB, Penicillium italicum Wehmer, and Aspergillus v. Tiegham BGB on various growth and yield parameters, including plant height, panicle size, shoot and root dry weight, and grain yield per plant. Additionally, we assessed their influence on the nutrient content of tef grains, specifically nitrogen (N), phosphorus (P), potassium (K), magnesium (Mg), calcium (Ca), zinc (Zn), and iron (Fe). Results showed that Trichoderma harzianum Rifai BGB and Penicillium italicum Wehmer significantly (P<0.001) enhanced plant height, panicle size, and the number of fertile tillers compared to the control and Aspergillus. Both fungi also significantly increased shoot and root dry weight, as well as grain yield per plant. Regarding nutrient uptake, Trichoderma and Penicillium markedly improved nitrogen, phosphorus, magnesium, calcium, zinc, and iron content in the grains. Penicillium showed notable improvements in these nutrients compared to the control and Aspergillus, while Trichoderma was superior in nitrogen content. Our findings suggest that Trichoderma harzianum Rifai BGB and Penicillium italicum Wehmer are effective in promoting tef growth, enhancing yield, and improving grain nutritional quality. These results indicate the potential of using these fungi as biofertilizers to optimize tef cultivation and address nutrient deficiencies in tef grains